Implementation of Kurikulum Merdeka on Student Interest and Learning Outcomes at MI Islamiyah Pucangtelu (AJER: Advanced Journal of Education and Religion, 2024)
The curriculum plays an important and fundamental role in the world of education. The curriculum is considered the soul and the learning process is considered the body. Changes to the education curriculum in Indonesia are another effort to improve the quality of education. The curriculum must continuously change or develop in order to find the right curriculum system to use in accordance with the conditions of students, teaching staff, available educational facilities and current developments. The aims of this writing are: (1) To analyze the extent of the implementation of the independent curriculum at MI Islamiyah Pucangtelu. (2) To determine the interests and learning outcomes of students at MI Islamiyah Pucangtelu after implementing the independent curriculum. In this thesis research, the author used a descriptive qualitative method where data collection used observation, interview and documentation techniques. Data were analyzed using data reduction methods, data presentation and drawing conclusions. From the results of this research, it can be seen that, (1) The implementation of the independent curriculum at MI Islamiyah Pucangtelu is proceeding according to the stages set by the government in accordance with the regulations of Educational Institutions under the auspices of the Ministry of Religion because MI Islamiyah Pucangtelu is a madrasa-based school. The implementation of the independent curriculum at MI Islamiyah Pucangtelu is implemented in stages at grade 1, 2, 4 and 5 because it is still in the process of adjustment. Evidence of the implementation of the independent curriculum at MI Islamiyah Pucangtelu, the project program for implementing the Pancasila student profile. Apart from that, the learning administration at MI Islamiyah Pucangtelu has implemented administrative rules in the independent curriculum, namely the existence of learning objectives, the flow of learning objectives, the existence of teaching modules and learning assessments. (2) The interests and learning outcomes of students at MI Islamiyah Pucangtelu after the implementation of the independent curriculum had a positive impact on the quality of students' education. This is proven by the results of researchers' interviews with students who stated that their learning motivation increased because the learning implemented in class was much better. Apart from that, the learning outcomes of students at MI Islamiyah Pucangtelu were also better after implementing the independent curriculum.